Evaluation of the Effectiveness of the Regional Government Information System (SIPD) in Indonesia - Desak Gede Fianda Intan Nareswari; I Kadek Rian Prayana (International Journal of Public Administration and Policy, 2026)
The acceleration of digital transformation in the public sector has positioned information systems as a critical instrument for improving government performance. One of Indonesia’s strategic initiatives in this area is the implementation of the Regional Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD), which integrates planning, budgeting, administration, and reporting processes across local governments. This study aims to evaluate the effectiveness of SIPD implementation in Indonesia by examining system performance, user acceptance, and institutional readiness. Using a qualitative descriptive approach, data were collected through literature review, policy documents, and relevant empirical studies published between 2022–2025. The findings indicate that SIPD contributes positively to data integration and transparency; however, challenges remain in terms of system latency, centralized architecture constraints, and uneven human resource capacity across regions. These issues affect the optimal utilization of SIPD at the local government level. The study concludes that while SIPD has strengthened the foundation of digital governance in Indonesia, continuous system refinement and capacity building are required to enhance its effectiveness and sustainability.